Analysis of the Relationship Between Professional Ethics and Teamwork with the Mediating Role of Teachers’ Social Responsibility in Iraq - Shakir Kareem, Qays; Saeidian Khorasgani, Narges; Merzah Hamzam, Jinan; Ghashghaeizadeh, Nasrolah (Assessment and Practice in Educational Sciences, 2025)
This study was conducted with the aim of determining the relationship between professional ethics and teamwork with the mediating role of social responsibility among teachers in Babylon Province, Iraq. The study employed a correlational research design, and causal relationships among the variables of professional ethics, teamwork, and social responsibility were tested. The statistical population consisted of all teachers in the Department of Education of Babylon Province, totaling 530 individuals for the 2024–2025 academic year. Based on Krejcie and Morgan’s (1970) sampling table, a sample of 227 teachers was determined and selected through a non-random sampling method. Data were collected using standardized questionnaires, including the Professional Ethics Questionnaire by Armito et al. (2011), the Teamwork Questionnaire by Lencioni (2004), and Ahmadi’s (2009) Social Responsibility Questionnaire. The reliability coefficients for these instruments were 0.78, 0.72, and 0.87, respectively. The face validity of the questionnaires was confirmed by several individuals similar to the target sample. After data collection, descriptive analyses were conducted using the Statistical Package for the Social Sciences (SPSS, version 23), and inferential analyses, including Pearson correlation, structural equation modeling, and analysis of variance, were performed using PLS software. The results revealed a significant positive relationship between professional ethics and social responsibility (r = 0.623). Moreover, a significant relationship was found between social responsibility and teamwork (r = 0.259). Additionally, professional ethics and teamwork showed a significant relationship through the mediating role of social responsibility (r = 0.117). Based on these findings, it can be concluded that in order to strengthen teamwork among educational professionals, sufficient investment should be made in promoting teachers’ professional ethics, as professional ethics not only directly but also indirectly—through enhancing social responsibility—reinforces teachers’ teamwork behavior.